SISTEM RESIRKULASI DENGAN MENGGUNAKAN FILTER YANG BERBEDA TERHADAP PERTUMBUHAN BENIH IKAN NILA (Oreochromis niloticus) - Mulyadi .; Usman Tang; Elda Sri Yani (Universitas Sriwijaya, 2014)
ABSTRACT The research was conducted at Technology Aquaculture Laboratory, Fisheries and Marine Science Faculty, University of Riau. The purpose of the research was to determine the effect of water filter system that can improve water quality parameters in tilapia fish aquaculture. The research method was experiment with three treatments and three replications. Recirculation system using (P1) coral reef, graves, sand and fiber of palm tree, where a thickness of each filter material was 3 cm. While the recirculation system using aquaponic system (P2) using water spinach and P0 recirculation system using sponge. Treatment of P1 gave the best results of water quality, temperature 25-29 Â° C, pH 5-7, DO 4.1-5.3 mg/L, CO2 5.40- 8.90 mg/L, ammonia (NH3) from 0.10- 0.60 mg/L, the average absolute growth rate of 4.50 g, the average length of 7.29 cm and survival rate 100 %. Keywords : Resirculation system, water quality, tilapia